Relationship between firm performance and stock return of listed beverage food and tobacco companies in sri lanka - Mayuri, T.; Sulojana, G. (University of Jaffna, 2016)
All organizations and managers engage in increasing the value of stocks since the stock return has a great deal with the success of the organization. Stock returns and firm performance are two important parts of an organization. One of the most significant strength of any corporation is its performance, which means, how an organization has financially and non-financially performed during its operating period. Performance of firms is of vital importance for investors, stakeholders and economy at large. Stock return is another key factor in the decision of the stock. Stock return is generally equal to the stock price changes and dividend paid for that stock during its operating period. The present study examines the performance of the firm and its association with stock return for 19 Sri Lankan listed beverage food and tobacco companies for the period of 2010 to 2014 by using convenient random sampling for the purpose of data analysis. The hypotheses are examined with help of Pearson's correlation and regression analysis. This study considers return on equity, return on assets and asset turnover as independent variable and annual stock return as dependent variable where as firm size and leverage is controlling variables. Data was collected from listed company's annual reports and journals. Results of the study indicate that return on assets and return on equity are positively correlated with stock return as well as firm performance has no significant impact on stock return. The findings of the study will help future theorists and will be useful to the academicians, practitioners and managers.
Keywords: Asset turnover; Firm performance; Return on equity; Return on asset; Stock return